Cohesion and Proximity in Libyan Social Space: A Socio-Historical Approach to Interpreting the Libyan Crisis in the Production of Shared Cultural Meaning: Cohesion and Proximity in Libyan Social Space (Journal of Humanitarian and Applied Sciences, 2026)
This study investigates Libyan social space from a socio-historical and symbolic perspective. Space is viewed as a social construct reflecting history, symbols, and relationships, rather than merely a physical area. This study draws on Henri Lefebvre's ideas that space is a social product expressing lifestyles and perceptions. Accordingly, this study aims to understand the Libyan crisis through a disruption in the production of this space, focusing on the relationship between cohesion and proximity as analytical tools derived from physics. In this way, the Libyan crisis is considered a product of transformations in the symbolic and social structure, leading to challenges in constructing shared meanings and social unity. Thus, the Libyan crisis is understood as a crisis in the production of social space and a symbolic struggle over its meanings and representations.
Keywords: Social space; Sociological analysis; Western philosophical thought; Semantic space